A Moveable Benefit? Spillover Effects of Quotas on Women's Numerical Representation. (June 2023) - Kaur, Komal Preet; Philips, Andrew Q.
Abstract Quotas have helped women achieve greater numerical representation in government around the world. Yet do they have indirect effects on representation elsewhere? We take advantage of plausibly exogenous variation in when and which states enacted legislation mandating 50% women's representation in the lowest level of government in India to analyze how quotas affect women's candidacy, vote share, and winning probability at the state level of government. We find that women are more likely to compete and win for the higher political office when women reservation is implemented at the local levels of political governance. This suggests that gender quotas have spillover effects onto other levels in politics. As women continue to be under-represented in politics, this paper highlights the role of policy instruments in shaping political careers for women and building inclusive political institutions.